Exploring the antimicrobial peptidome of nematodes through phylum-spanning in silico analyses highlights novel opportunities for pathogen control. - Allister Irvine; Sharon A Huws; Louise E Atkinson; Angela Mousley (PLoS Neglected Tropical Diseases)
Antimicrobial Peptides (AMPs) are key constituents of the invertebrate innate immune system and provide critical protection against microbial threat. Nematodes display diverse life strategies where they are exposed to heterogenous, microbe rich, environments highlighting their need for an innate immune system. Within the Ecdysozoa, arthropod AMPs have been well characterised, however nematode-derived AMP knowledge is limited. In this study the distribution and abundance of putative AMP-encoding genes was examined in 134 nematode genomes providing the most comprehensive profile of AMP candidates within phylum Nematoda. Through genome and transcriptome analyses we reveal that phylum Nematoda is a rich source of putative AMP diversity and demonstrate (i) putative AMP group profiles that are influenced by nematode lifestyle where free-living nematodes appear to display enriched putative AMP profiles relative to parasitic species; (ii) major differences in the putative AMP profiles between nematode clades where Clade 9/V and 10/IV species possess expanded putative AMP repertoires; (iii) AMP groups with highly restricted profiles (e.g. Cecropins and Diapausins) and others [e.g. Nemapores and Glycine Rich Secreted Peptides (GRSPs)] which are more widely distributed; (iv) complexity in the distribution and abundance of CSαβ subgroup members; and (v) that putative AMPs are expressed in host-facing life stages and biofluids of key nematode parasites. These data indicate that phylum Nematoda displays diversity in putative AMPs and underscores the need for functional characterisation to reveal their role and importance to nematode biology and host-nematode-microbiome interactions.